Try and stick with it - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit, 2004)
A young boy learns the importance of trying new things and sticking with them even when they are difficult. Includes activities.
Book Links (A.L.A.)
2.0
K-3
K-3
Keywords: Determination (Personality trait) -- Juvenile literature; Persistence -- Juvenile literature; Determination (Personality trait); Persistence; Determination; Persistence